Transformasi Masyarakat Akibat Keberadaan Tambang Emas: Studi Kasus di Dusun Tamsu, Desa Kasiro Kecamatan Batang Asai Kabupaten Sarolangun - Al Hadis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to explore and analyze in-depth the transformation of the Tamsu community due to the presence of gold mining activities in the surrounding area. The research was conducted from May 2024 to July 2024 using a qualitative descriptive method. Data was collected through observation and interviews with key informants such as community leaders, village officials, miners, and the general public around the Tamsu Gold Mining Site. The results show that the presence of large-scale gold mining using modern equipment such as excavators has significantly transformed the socio-economic aspects of the Tamsu community. On one hand, there has been an increase in income for some community members who work in the mines. However, this has also led to negative impacts, such as illegal logging, loss of agricultural land, and water pollution.